Answer:
y - 3y^2 + 4y^2 - 12y
y^2 - 11y
Step-by-step explanation:
Answer:
x=-2 and x=0
Step-by-step explanation:
5(x-2)^2 = 20; divide by 5 both sides
(x-2)^2 = 4; take the square root of both sides
(x-2) = ±2, now set it equal to positive 2 and negative 2
x-2 = 2
x=4
AND
x-2 = -2
x=0
Answer:
The ratio 450 : 200 can be reduced to lowest terms by dividing both terms by the GCF = 50 :
450 : 200 = 9 : 4
Therefore:
450 : 200 = 9 : 4
basically 9/4
Step-by-step explanation:
The expression (-4x + 9)^2 cannot be equal to (-4x)^2 + 9^2 because it is actually equal to the product of two factors (3 + 2sqrt x) (3- 2 sqrt x). One cannot use obviously distributive property. Hence the answer to this problem should be C. as she did not understand both perfect square trinomial and did not determine the product
<h2><u>Answer:-</u></h2>
Given:
Two angles form a linear pair.
It means sum of their measures = 180°.
And,
Measure of one angle is 24° greater than the other.
Let the other angle be x.
→ First angle = (x + 24)
According to the question,
<h3>→ x + x + 24 = 180</h3>
→ 2x = 180 - 24
→ 2x = 156
→ x = 156/2
<h3>→ X = 78°</h3>
<u>There</u><u>fore</u><u>,</u>
- 1st angle = 78°
- 2nd angle = 78° + 24° = 102°